Assessment of radiation safety perimeter for a radiological emergency management involving RDD explosion in metropolitan area, based on Gaussian dispersion model. (2015) - Pandey, Alok; Kim, Hong Suk
In the event of a radiological dispersion device (RDD) explosion, a safety perimeter is the important factor to restrict the public in the area of high radiation exposure. Establishment of the safety perimeter to initiate emergency actions by the emergency management team is a crucial task, in a very short time and with very limited information about the explosion. The safety perimeters in case of RDD explosion have been evaluated in this study, on the basis of internationally recommended ambient dose rate, in different formulated scenarios with 137 Cs, 60 Co and 90 Sr sources with different quantities of explosive. Result shows the safety perimeter is less for higher explosive quantity for all the sources. The evaluated perimeters are found to be less than reference generic values, for RDD scenarios involving 137 Cs and 90 Sr sources. However for 60 Co source, the evaluated safety perimeters are found to be about 1.4-2.0 times higher than the reference generic perimeter.